(untitled) (Annals of Medical Research, 2021)
One hundred healthy hepatitis B virus (HBV) seronegative persons were enrolled in a single blind randomized study to compare antibody and clinical responses to yeast recombinant S antigen vaccine (YSHBV) (Hepavax-gene, 1 ml: 20 mgr = one dose) and Chinese hamster ovary cells (CHO) recombinant Pre S2 + S vaccine (CS2SHBV) (Genhevac B, 0.5 ml: 20 mgr = one dose). 50participant (group I) received 20 mgr of YSHBV by intramuscular (IM) injection at 0h,1st and 6th months (mo). 50 participants (group II) received 20 mgr of CS2SHBV by IM injection at 0th, 1st and 2nd mo. Serological and biochemical responses were measured at 0h, 1st, 2nd, 3rd, 6h and 7th months in both groups. The proportion of vaccines with minor local complaints (mainly local pain, myalgia ) and proportion developing antibody to surface antigen (anti- HBs) were similar for both vaccine groups (p >0.05), but anti-HBs titers were generally higher among recipients of CS2SHBV. Anti-HBs developed in 92% and 96%, in group I and II by 7th month, respectively. These data imply that YSHBV vaccine is as well tolerated and immunogenic as CS2SHBV vaccine. However, further studies are necessary to compare the duration of immunity after vaccination for two vaccines.